2015
DOI: 10.4049/jimmunol.1402219
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Mediate Protective Immunity against Secondary Nematode Infection

Abstract: Eosinophils are versatile cells that regulate innate and adaptive immunity, influence metabolism and tissue repair, and contribute to allergic lung disease. Within the context of immunity to parasitic worm infections, eosinophils are prominent yet highly varied in function. We have shown previously that when mice undergo primary infection with the parasitic nematode, Trichinella spiralis, eosinophils play an important, immune regulatory role that promotes larval growth and survival in skeletal muscle. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 58 publications
(83 reference statements)
2
45
0
Order By: Relevance
“…Classic in vitro studies described the anti-helminthic actions of eosinophils co-cultured with antigen-specific antibodies and complement(97, 98). These results are supported by in vivo studies showing the essential contribution of eosinophils to mediate protection against reinfection with N. brasiliensis and T. spiralis (99, 100). Furthermore, expression of MHC-II and co-stimulatory molecules on activated eosinophils following infection with T. muris and Brugia malayi (101, 102) suggests that eosinophils might contribute to establish long-term protection against helminths by promoting adaptive immune responses.…”
Section: Innate Immunitysupporting
confidence: 56%
“…Classic in vitro studies described the anti-helminthic actions of eosinophils co-cultured with antigen-specific antibodies and complement(97, 98). These results are supported by in vivo studies showing the essential contribution of eosinophils to mediate protection against reinfection with N. brasiliensis and T. spiralis (99, 100). Furthermore, expression of MHC-II and co-stimulatory molecules on activated eosinophils following infection with T. muris and Brugia malayi (101, 102) suggests that eosinophils might contribute to establish long-term protection against helminths by promoting adaptive immune responses.…”
Section: Innate Immunitysupporting
confidence: 56%
“…Indeed, both IL-5 and eosinophildeficient mice harbor increased numbers of N. brasiliensis larvae after secondary infection, 89 with similar results during secondary T. spiralis infection. 200 Furthermore, eosinophils negatively regulate Th17 cells 201 and promote the expansion of regulatory T cells in the steady state 198,202 that might affect overall inflammation, illustrating their complex contribution to tissue homeostasis. Similarly, whereas resident intestinal macrophages are mostly suppressive in nature and do not act inflammatory to pathogen stimulation, type 2 cytokines give rise to alternatively activated macrophages that might contribute to the expulsion of certain parasites.…”
Section: Resolutionmentioning
confidence: 99%
“…In secondary subcutaneous larval infection with Nippostrongylus brasiliensis , increased numbers of larvae migrate to the lungs in IL-5 −/− and ΔdblGATA mice [43]. Similarly, migration of Trichinella spiralis newborn larvae is increased in ablated versus WT mice and muscle larvae burdens are increased in ΔdblGATA mice upon secondary infection [45]. Earlier reports showed that eosinophils attach to newborn T. spiralis via specific antibodies, degranulating and killing the larva.…”
Section: Secondary Infection: Confirming the Dogma In Vivomentioning
confidence: 99%
“…Earlier reports showed that eosinophils attach to newborn T. spiralis via specific antibodies, degranulating and killing the larva. Protection by eosinophils and antibodies has been documented in vivo by transferring sera or immunoglobulin from infected mice together with eosinophils to naïve ΔdblGATA mice prior to infection [45]. Although both EPX and MBP are toxic for newborn Trichinella in vitro , mice deficient in EPX or MBP show similar resistance to reinfection that is comparable to wild type mice (WT) (Figure 1).…”
Section: Secondary Infection: Confirming the Dogma In Vivomentioning
confidence: 99%
See 1 more Smart Citation